STRATEGI BANK KALBAR SYARIAH CABANG SINGKAWANG DALAM MENARIK MINAT NASABAH MENGGUNAKAN LAYANAN MOBILE BANKING - Sonia Sebty De Lang Lang Buana; maskupah; wahab (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
This study aims to determine the strategy of Bank Kalbar Syarih Singkawang Branch in attracting customers to use Mobile Banking services. This research, including descriptive qualitative research, with a total of 10 informants, describes situations or events that come from observations, interviews and documentation. The data sources used are primary data obtained directly in the field, secondary data obtained from books, the internet and previous research. The results of this study indicate that the strategy of Bank Kalbar Syariah Singkawang Branch in increasing Mobile Banking users is by means of a promotion strategy. This research shows that customers' interest in using Mobile Banking services at Bank Kalbar Syariah Singkawang Branch is influenced by internal factors and partly influenced by external factors.